ENVIRONMENTAL ECONOMICS: welfare economics in focus - Barros Neto, Jahy; Fontgalland, Isabel Lausanne (Revista Interface Tecnológica, 2023)
The central tenets of this work relate that environmental problems have their roots in the failure of economic systems to maximize human well-being, that environmental quality is important for that well-being and for the goals of more traditionally oriented economic growth, and that efficient policies can be achieved through incentives. In order to carry out this article, a bibliographical review methodology was used, with the work An Intellectual History of Environmental Economics, by David Pearce, being essential for understanding. The content is divided into: The Origins of Environmental Economics in the introductory part; Sustainable Development; Economic Evaluation; Cost-Benefit Analysis; Choice of Policy Instruments; and Ecological Economics. As a conclusion, it is possible to appreciate trends in economic-ecological thinking.